2016
DOI: 10.1108/wjstsd-01-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Consumer knowledge in pro-environmental behavior

Abstract: Purpose Environmental behavior studies suggest that knowledge, in addition to other psychological and social factors, can play an important role in consumers’ environmental behavior change. The purpose of this paper is to understand the relationship between knowledge and various psychological factors which encourage consumers’ participation in pro-environmental behaviors. The relationships that link an individual’s attitudes toward science, environmental values, different types of knowledge (i.e. scientific fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 60 publications
(116 reference statements)
2
14
0
1
Order By: Relevance
“…When a person has a higher level of subjective and objective environmental knowledge, non-anthropocentric concern, and willingness to pay for the environment, he or she practices a higher level of PEB. These results are like the previous research [22,32,36,54], confirming the positive effects of individual psychological factors on PEB.…”
Section: Estimation Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…When a person has a higher level of subjective and objective environmental knowledge, non-anthropocentric concern, and willingness to pay for the environment, he or she practices a higher level of PEB. These results are like the previous research [22,32,36,54], confirming the positive effects of individual psychological factors on PEB.…”
Section: Estimation Resultssupporting
confidence: 91%
“…Specific factors for each category come from a review of existing studies, even if each of the studies deals with only some factors. Primarily, environmental attitude and environmental knowledge are listed as the personal determinants of PEB in the literature [19][20][21][22][23][24][25][26]31,32]. Specifically, researchers generally categorize environmental attitude into sub-types of environmental concern, environmental risk perception, and willingness to pay for environment conservation, and environmental knowledge into subjective and objective knowledge.…”
Section: Theories On Pebmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental knowledge is widely viewed as the basis for encouraging participation in environmental protection activities [54]. Onel and Mukherjee [64] indicated that, when an individual possesses more scientific knowledge or is more familiar with environmental issues, he or she is more willing to pay higher taxes to protect the environment, pay higher prices to purchase environmentally-friendly products, and are even willing to reduce personal living needs.…”
Section: Environmental Knowledge Emphasized By Traditional Models Wasmentioning
confidence: 99%